The Sokovia Accords and the Limits of Power: Captain America and Reflections on the Role of the Superpower in the International System - Klein Garcia, Liliane (Faculdade de Filosofia e Ciências, 2020)
Observing the unipolar system emerging from the closure of the Cold War, is remarkable the sentiment of geopolitical insecurity generated by the existence of only one global superpower and the doubts about the role of the sovereign State in such system. In this paradigm, Captain America: Civil War is released with a contesting symbology about the role of the hegemon in the international system. Therefore, first it is exposed the movie plot, followed by the liberal and realist theories of international relations and the French semiotics. With this in mind, the symbols in the feature are analised and, in conclusion, it is stated that the authors wish to convey a message in bipartisan union amongst the American people.